THE INFORMATION SYSTEMS OF ROADS AND BRIDGES IN KATINGAN - Dewi Untari (Lambung Mangkurat University Press, 2014)
Infrastructure data management of roads and bridges is still done manually so that the data have not been well documented. The objective of the study is to develop the information system of roads and bridges in Katingan. This study uses survey and case studies. The survey was conducted to collect primary data i.e. the infrastructure data of roads and bridges. The case study was carried out in the handling of road and bridge infrastructure activities in the Dinas Pekerjaan Umum Kabupaten Katingan. The research was conducted through six stages, namely literature review, identification of system information, system design, system implementation, validation and verification of the system, and the conclusions and suggestions. The result of this research is the information system of road and bridge and it was named SIIJABAT. SIIJABAT is able to provide information about the handling of road and bridge infrastructure in Katingan, which is divided into north and south parts, which consists of 16 roads and includes the handling of information of roads and bridges from 2003 to 2009. SIIJABAT can be used to assist management in determining policy on road and bridge infrastructure in Katingan.